Warunkowe umorzenie postępowania jako szczególny środek odpowiedzialności karnej - Wiśniewska, Milada (Prawo Kanoniczne, 2010)
The subject of this study is a conditional discontinuance of legal proceedings as one of the measures related with giving the perpetrator a probation. It firstly has been introduced to Polish penal system in 1969. This solution seems to be very specific comparing to the others as it exists as a conditional discontinuance of legal proceedings as well as a parole, or conditional release from serving the full sentence. Further development of this probational measure took place in 1997 as a part of a wider amendment of Polish Penal Code (Kodeks Karny). Art.66 defines the conditional discontinuance of legal proceedings. A verdict ajudicated on a basis of articles 341 § 5 and 414 § 1 KPK (Code Of Penal Rules) and conditionally discontinuing the legal proceedings is a verdict confirming the perpetration of a criminal offence, although is not the conviction itself. Conditional discontinuance of legal proceedings’ function is to give a perpetuator a chance for unpunishability and a clear criminal record after committing the crime in exchange for not breaking the law in the future. Positive expired probation ex lege shapes the conditional discontinuance into a final one. Main reason for this study is to discuss the articles: 66-68 of Polish Penal Code. The above articles are regulating the matter of the conditional discontinuance of legal proceedings. The research is being divided into four topically related sections. Section one are simply introduction remarks. Section two describes the circumstances for use of conditional discontinuance of legal proceedings. The circumstances might be categorized into three groups: crime related, perpetrator related and finally – case related. To specify, all of the liability circumstances must be determined for legal use of conditional discontinuance of legal proceedings. Moreover, the circumstances are supposed to occur in a cumulative manner. Section three depictures the duties on a probation and the effects of its progress. Finally section four defines reasons for taking legal actions. The study finishes with a short summary of all discussed topics. It also questions why, if it is such a charity, the courts who are up for judgement practically do not apply for this solution. What reason lies behind this conditon?